Optimization of Enzymatic Hydrolysis Process, Structural Characterization and Antioxidant Activity Analysis of Gastrodia elata Polysaccharide - Yunfei HU; De ZHOU; Qinglan ZENG; Jinsong HE; Ming ZHAO; Qingyan TANG (Shipin gongye ke-ji)
Polysaccharides are attracted much attention because of their diverse biological activities. However, natural polysaccharides tend to have high molecular weights, resulting in their low solubility and bioavailability. In this study, α-amylase was used to degrade polysaccharides derived from Gastrodia elata, and the enzymatic hydrolysis process was optimized based on the yield of reducing sugars. G. elata polysaccharides were prepared under the optimal conditions for enzymatic hydrolysis. Their dissolution rate, monosaccharide composition, relative molecular weight, functional groups, and microstructure were analyzed before and after enzymatic hydrolysis. In addition, the ABTS+ and DPPH free radical scavenging abilities in vitro were tested before and after enzymolysis. Results revealed that the optimal enzymolysis process was as follows: enzyme dosage, 460 U/g, enzymolysis time, 100 min, enzymolysis temperature, 60 ℃, enzymolysis pH, 5.4. Under these conditions, the yield of reducing sugars after enzymolysis was 0.441 mg/mL. After enzymatic hydrolysis, the dissolution rate of G. elata polysaccharides increased from 81.28% to 93.57%. The monosaccharide composition and functional group structure indicated no obvious changes, except that the molecular weights of the two polysaccharide components were substantially reduced (P<0.05), and the mesh structure of G. elata polysaccharides was destroyed and changed into sheet structure. In addition, the antioxidant activity of G. elata polysaccharides was considerably enhanced after enzymatic treatment (P<0.05). This study provides a scientific basis for the enzymatic degradation of G. elata polysaccharides.